Integrated application of biochar and bio-fertilizer improves yield and yield components of Cowpea under water-deficient stress - Mousavi, Seyed Afshin; Shokuhfar, AliReza; Lak, Shahram; Mojaddam, Mani; Alavifazel, Mojtaba (Italian Journal of Agronomy, 2020)
A low amount of organic matter and insufficient irrigation are two main challenges facing successful crop production in arid and semiarid regions. Application of biochar as an organic amendment to soil not only can help increase organic matter in soil, but also may alleviate adverse effects of water deficit on plant growth and yield production. To test this hypothesis, a two-year field experiment was conducted to assess the effect of sugarcane biochar on yield and yield components of cowpea in water-deficient soil. Treatments consisted of two levels of seed treatment with nitroxin, three levels of biochar application (0, 4, and 8 ton/ha), and a threelevel irrigation regime (60, 90, and 120 mm from evaporation pan class A), laid out in a split-factorial design. Results showed that the seed number per plant was significantly higher in cowpea when grown with biochar, possibly due to the relief of water-deficient stress and higher phosphorus and potassium content. Biomass production of cowpea declined under a severe waterdeficit condition (ir3) compared to normal irrigation (ir1) in 2018 and 2019, decreasing by 39% and 42%, respectively. The maximum biomass obtained from application of 8 ton/ha biochar reached 617.43 and 664.92 g/m2 in 2018 and 2019, respectively. Seeds treated with nitroxin exhibited 10% and 8% greater biomass production in 2018 and 2019 as compared with control treatments. Seed yield increased with the addition of biochar to soil under all irrigation regimes; however, the maximum seed yield of 266.46 and 275.36 g/m2 was observed when there was no water-deficient stress condition and application of 8 ton/ha biochar in 2018 and 2019, respectively.